Ensino de cultura e gêneros textuais: as crenças de uma aluna-professora de língua estrangeira - Aguiar, Marcia Juliana Dias de (2005)
The aim of this dissertation is to verify the beliefs of a Language Course undergraduate student in a university in Santa Maria, who has already been teaching English, about EFL practices involving culture. Such a practice is based on an intercultural perspective taking into consideration a critical and reflexive analysis of the sociocultural content reflected in textual genres. In this context, the methodology used to gather data was action-research (Burns, 1999; Kemmis & Mc Taggart, 1988), which has as a main point the reflexive and colaborative work as a way to improve teaching conditions. In addition, action-research was associated with Porlán & Martin (1997) and Liberalli (1999) principles about teacher s diaries as an instrument to reflect and support teacher betterment. To the data analysis, it was found theoretical support in the cues method principles (Ginzburg, 1989), as well as in James Gee (1999) discourse analysis as a way to detect in the student-teacher Discourse beliefs, values, feelings, identity characteristics, which could be influencing her classroom practice. From the preintervention, intervention and post-intervention phases, it was possible to make evident the student-teacher beliefs considering a classroom practice covering culture and textual genre work and how this process was planned, acomplished and significant to her.